O conceito de eutanásia em Ronald Dworkin - Cauduro, Joseane (My University, 2015)
The present dissertation deals with the euthanasia’s problem. The biomedical technology advanced to much in these last two decades, in the good one and bad one way. Is is thanks to this new technology that many sick people have been safe of its disease. However, in the another way, this same technology has been slaving thousand of lives, to live without any cure’s perspective or health’s improves, only prolonging those lifes and those suffering. In this context, it tries to bring to the scientific community and for all students, the Law’s Theories of Ronald Dworkin, a very famous author, to make possible to show how he sees and undestands Law. And then, presents his vision concerning the euthanasia institute. After that, it displays the Dworkin’s proposal in face of euthanasia order, as wel as brings his proposal for the brazilian reality, verifying the possibility of it is implementation face the current Law. It is expects with this work to provide plus a new source of knowledge to instigate the reflection concerning the euthanasia in our society. The reflection is very important because deaths is part of ours lifes.
A presente dissertação investiga o problema da eutanásia. A tecnologia biomédica avançou nestas últimas duas décadas de forma notável, no bom e no mau sentido. É graças a esta tecnologia que muitos e muitos doentes têm sido salvos de suas enfermidades transitórias, porém, de outro lado, estas mesmas medidas, escravizam milhares de vidas a serem vividas sem qualquer perspectiva de cura ou melhora, somente prolongando a vida e o sofrimento de pacientes terminais. Nesse contexto, buscou-se trazer para conhecimento de toda comunidade científica, bem como dos estudantes de direito e afins, as teorias de direito do notório autor Ronald Dworkin, para possibilitar, num primeiro momento, demonstrar como este vê e entende o Direito e para, após, apresentar sua visão acerca do instituto da eutanásia. Por fim, expor a proposta de Dworkin em face de pedidos de eutanásia, bem como trazê-la para a realidade brasileira, verificando a possibilidade de sua implementação face à legislação vigente. Ressalta-se que se espera com este trabalho proporcionar mais uma fonte de conhecimento, para instigar a reflexão acerca da eutanásia em nossa sociedade, uma vez que é realmente necessária já que a morte é um processo vital pelo qual todos nós passaremos.
Keywords: Dworkin, Ronald William; Eutanásia; Dignidade (Direito); Direito; Euthanasia; Respect for persons - Law and legislation; Law